Tathwir al-Mawad al-Taklimiyah lo Maharah al-Kalam 'Ala Asas al=Mawaqif - Mabrurrosi, Mabrurrosi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
The development of instructional materials is an important endeavor and plays a significant role in ensuring the success of the teaching and learning process. The instructional materials found by the researcher in the prescribed textbook for teaching speaking skills to students of the Arabic Language Center at Darul Ulum Banyuanyar Islamic Institute, Pamekasan, are limited and do not accommodate students’ needs for oral practice according to their communicative situations, which would otherwise contribute to the development of their speaking ability. The textbook is confined to dialogues only and merely presents vocabulary scattered across each page. This condition may lead to students’ failure in learning speaking skills. This study aims to develop, produce, and evaluate instructional materials for speaking skills for students of the Arabic Language Center at Darul Ulum Banyuanyar Islamic Institute, Pamekasan, East Java, in order to improve their speaking and communication skills in accordance with their daily situations. The research approach employed is both quantitative and qualitative, using the Research and Development (R & D) methodology. The results of the study can be summarized as follows: (1) The procedures for developing instructional materials for speaking skills for students of the Arabic Language Center at Darul Ulum Banyuanyar, Pamekasan, include needs analysis, planning and design, material development, expert validation, revision and correction, field testing, and final revisions and corrections. (2) The newly developed instructional materials proved effective in improving students’ ability in oral expression in terms of Arabic pronunciation, fluency, and their ability to use vocabulary. This is evident from the comparison between the pre-test and post-test results, where the calculated t value (93.3) is greater than the t table value at the 99% significance level (2.83).